The Effect of Work Environment, Organizational Commitment and Compensation on Employee Performance at Aisyiyah St. Khadijah, Pinrang District - Herman, Saiful (PT. Maju Malaqbi Makkarana, 2023)
This study aims to (1) examine and analyze partially and simultaneously the influence of the work environment, organizational commitment and compensation on employee performance. This research was conducted at St. Aisyiyah General Hospital. Khadijah Pinrang District by taking 86 employees as research samples. The results of this study indicate that (1) partially the work environment and organizational commitment variables significantly influence employee performance, while the compensation variable has no influence on employee performance at St. Aisyiyah General Hospital. Khadijah Pinrang District (2) simultaneously the work environment, organizational commitment and compensation significantly influence the performance of employees of St. Aisyiyah General Hospital